Підходи до оцінки неоднорідності системи регіональних ринків праці України - Нікіфорова, О.В. (Культура народов Причерноморья, 2013)
Підніматься питання про необідність відмінносте у підода до порівняльної оцінки регіональни ринків праці та оцінки неоднорідності розвитку системи регіональни ринків праці. Пропонуться набір індикаторів для оцінки неоднорідності функціонування системи регіональни ринків праці в країні. к метод оцінки неоднорідності пропонуться використовувати систему коефіцінтів варіації. рамка запропонованого підоду проводиться оцінка неоднорідності розвитку системи регіональни ринків праці країни за ряд років. Поднимается вопрос о неободимости различи в подода к сравнительно оценке региональны рынков труда и оценке неоднородности развития системы региональны рынков труда. Предлагается набор индикаторов для оценки неоднородности функционирования системы региональны рынков труда в краине. Как метод оценки неоднородности предлагается использовать систему коффициентов вариации. В рамка предлоенного подода проводится оценка неоднородности развития системы региональны рынков труда краины за ряд лет. The heterogeneity of the system of regional labor markets is the basis for the possible formation of ethnic, national, economic, and political conflicts. This makes it necessary to development of an approach to the assessment of homogeneity of such complex socio-economic system as a national labor market. The issue of the need to making differences in metodical approaches to comparative assessment of regional labor markets and assessment of heterogeneity of the system of regional labor markets is raised in the article. The set of indicators to assess the heterogeneity of the system of regional labor markets in Ukraine is proposed in the article. The system of coefficients of variation is suggested to use as a method of evaluating heterogeneity of the system of regional labor markets in Ukraine. The proposed approach assesses the heterogeneity of the system of regional labor markets of Ukraine for a number of years. It was revealed that the regional labor markets of Ukraine differ in their development in terms of wage arrears and migration. On indicators of unemployment, employment and working conditions is planned reduction of heterogeneity of the national system of labor markets